PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, DAN FASILITAS KANTOR TERHADAP KINERJA PERANGKAT DESA DI KECAMATAN KAMPAR - Dedy Wahyudi; Abshor Marantika; Yusup Yusup (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
Organizations in achieving goals with all the processes require a leadership role. Through capable leaders, they can directly monitor and direct and provide positive input for their employees. This will raise the interest of employees to work harder and produce maximum work results. The work environment needs to be considered to improve performance, because agencies that have a good and comfortable work environment will motivate their employees to work more enthusiastically and passionately. In addition, work facilities are also very necessary in improving the performance of village officials, with complete work facilities, it is hoped that it will be very helpful in completing office tasks so that the resulting performance will be maximal. The purpose of this study was to determine whether there was an influence of leadership, work environment, and office facilities on the performance of village officials in Kampar District. The population in this study were all village officials in the Kampar sub-district, as many as 189 village officials. While the samples taken were 128 village officials obtained from the Slovin formula with an error rate of 5%. The data collection method used in this research is using a questionnaire/questionnaire. Data analysis used descriptive percentage analysis method, multiple linear regression analysis, classical assumption test analysis, and hypothesis testing analysis with the help of SPSS program. The results of this study are that there is a positive and significant influence of leadership, work environment and office facilities on the performance of village officials in Kampar District. Suggestions in this study are suggested to village officials to optimize the use of windows as air ventilation and village office buildings in Kampar District need to be equipped with soundproofing. In addition, it is recommended that the village head completes and repairs social facilities that are felt to be lacking or have been damaged.